Keterangan Bebas Narkoba Bagi Calon Suami Sebagai Syarat Pernikahan Perspektif Maqashid asy-Syariah - Rizky Kurniawan; Milhan Milhan (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The community of Tanah Putih Tanjung Melawan District has required prospective husbands to have a drug certificate which has not been found in the regional regulations of Rokan Hilir Regency. From the results of sociological juridical research, it was found that community motivations include the increasing prevalence of drug use, the existence of religious commands to choose a good (pious) partner. Supporting factors in anticipating divorce caused by drugs from several aspects, namely the existence of good intentions, family cooperation, parental awareness, rare family objections, and daughters' obedience to parents. Inhibiting factors include being offended, prioritizing stability, dishonest grooms, rushing in carrying out marriages, the absence of regional regulations. This practice is in accordance with the maqashid asy-syari`ah, namely in terms of maintaining religion (hifz din) and protecting offspring (hifz nasl).